On the Mixture of Normal and Half-Normal Distributions. (20th June 2022) - Alruwaili, Bader; Alharbi, Randa; Hafez, E. H.; Riad, Fathy H.
Abstract : In this research, we studied the mixture of normal and half-normal distributions and introduced some properties for this mixture. In particular, we derived the mean, median, and mode of the mixture of normal and half-normal distributions. We also focused on exploring the Bayesian estimation of parameters of the mixture of normal and half-normal distributions by using different methods and then, using type-I censored sample units, presented a simulation study on the mixture of normal and half-normal distributions.